COMPARATIVE ANALYSIS OF UZBEK TRANSLATIONS OF THE HOLY QUR’AN - Numanov Ziyodbek Bahodirjonovich (Galaxy International Interdisciplinary Research Journal, 2021)
Tafsir of the Holy Quran in this article “Translation and commentary of the meanings of Al-Qur’an al-Karim” by Altynkhan Tora, “Tafsiri hilal” by Sheikh Muhammad Sadiq Muhammad Yusuf, “Qur’an by Mutallib Usmanov oni karim. Translation and Scientific-Historical Commentaries ”and other sources that are important sources in“ Quranic Studies ”and“ Islamic Studies ”.